STUDI ANALITIS MENGENAI PROSEDUR AKUNTANSI MUSYARAKAH DAN RELEVANSINYA DENGAN PSAK 106 PADA BANK SYARIAH TUNAS MUDA - Muhammad Maulana; Agustian Feri; Wafiqah Nur Azizah (UM. Bengkulu, 2025)
Applying Islamic accounting principles consistently is crucial to Islamic banking's ability to successfully serve the public. When presenting financial data and banking products based on fund raising and fund distribution, these principles are used as a guide. Using the requirements of PSAK No. 106, the main focus of this study is to assess the appropriateness of accounting implementation with relation to the recognition, measurement, presentation, and disclosure of financial statements of musyarakah financing. This study was carried out at Bank Syariah Tunas Muda. Both primary and secondary data sources were employed in this investigation. Interviews and documentation were the methods employed in this study to acquire data. Quantitative descriptive methods were employed in data analysis procedures. The purpose of this study is to assess if the Bank's musyarakah financing accounting procedures are appropriate for PSAK 106. We must utilize this strategy to determine the cause, regardless of whether this research is consistent or not. Keywords: Islamic Bank, PSAK 106, accounting for Musharakah